ANALISIS STRATEGI GURU DALAM MENANAMKAN NILAI KARAKTER â€œJUARAâ€ - Ramadhianti, Medina; Oktaviani, Maya; Faesal, Muhammad (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2023)
At the start of offline learning, there are still students who are carried away by the atmosphere of online learning and there is a decrease in the character of some students when learning online so the role of the teacher is needed to foster and develop the character of the students. This study aims to find out the strategies used by teachers in instilling JUARA character values in grade 8 students. This research was conducted from July to August 2022 at SMPN 252 Jakarta. The results of this study are: 1) in instilling honest character, the teacher uses an assessment rubric strategy (especially for English lessons), integrity pacts, personal correction, giving assignments, role models/examples, advice/appeals, 2) in instilling tenacious character, the teacher uses strategies by providing trust, examples/examples, group work, rote assignments (specifically Islamic religious lessons) and involving students in various activities, 3) in instilling a trustworthy character, teachers use strategies by giving responsibility, role models/examples, and appeals, 4) in instilling religious character, the teacher uses the tadarus Al-Quran strategy together, morning services (non-Muslims), holding congregational and dhuha prayers, getting used to praying before studying and going home, and holding events on religious holidays, and 5) in instilling active character , the teacher uses strategies by requiring mandatory and optional extracurriculars, Wednesday performance activities, group discussions, class pickets, healthy Friday activities, examples/examples, advice and the question and answer method.